Membaca Komentar di Media Sosial Sebagai Hiburan - Athifah Nur Husna; Puji Rianto (Program Studi Ilmu Komunikasi UII, 2021)
Social media gives various functions and uses for the users. The comment feature is one important aspect for its uses and gratification. This study applies the theory of Uses and Gratification and Media Entertainment to describe the uses and gratification of users in reading comments on social media and provide an overview of the behavior patterns of social media users at this time. This study used a qualitative approach with data collection techniques in the form of in-depth interviews and documentation collection. There are four uses and gratifications in reading comments on social media. The four uses and gratifications referred to information, perspective, entertainment and inspiration.